A gravity model under competition - Kari E. O. Alho (The Research Institute of the Finnish Economy (ETLA), 2004)
The paper presents an alternative derivation of the gravity equation for foreign trade, which is explicitly based on monopolistic competition in the export markets and which is more general than previously in the literature. In contrast to the usual specification, our model allows for the realistic assumption of asymmetry in mutual trade flows. The model is estimated for trade in Europe, producing evidence that trade flows and barriers do, indeed, reveal strong asymmetry. We then carry out a simulation, based on the estimated model, of general equilibrium effects, through trade, of possible UK entrance into EMU. – – Paperissa esitetään ulkomaankaupan gravitaatiomallin vaihtoehtoinen johtaminen, joka perustuu eksplisiittisesti monopolistisen kilpailuun vientimarkkinoilla ja joka on yleisempi kuin aiemmin kirjallisuudessa. Päinvastoin kuin tavanomaisesti, paperissa johdettu malli sallii realistisen oletuksen epäsymmetrisistä keskinäisistä kauppavirroista. Malli estimoidaan Euroopan kauppavirroille, ja estimointitulos antaa vahvistusta sille, että kauppavirrat ja kaupanesteet ovat todellakin selvästi epäsymmetrisiä. Sen jälkeen mallin avulla laaditaan simulointi siitä, millaiset yleisen tasapainon mukaiset vaikutukset ovat ulkomaankaupan muutosten kautta Ison-Britannian mahdollisesta liittymisestä EMUun. Kysymys kaupan esteiden asymmetriasta on jälleen varsin merkittävä tekijä integraatiopolitiikan vaikutusten selvittämisessä.
Keywords: F12; F15; 330; Gravity model; trade barriers; asymmetry; Gravitaatiomalli; kaupan esteet; epäsymmetria; Gravitationsmodell; Außenwirtschaft; Monopolistischer Wettbewerb; Schätzung; Europa